Informed Consent in Mental Health Research at Workplace - Beby Etika Sari Yudiarti; Ray Wagiu Basrowi (The Indonesian Journal of Community and Occupational Medicine, 2024)
Background: Ethical considerations and informed consent are crucial in mental health research within workplace settings. The disclosure of mental health issues, the impact of workplace factors, and the experience of stigma all play significant roles in the ethical management of mental health data and consent processes. Objective: This review aims to describe ethical issues and challenges related to informed consent in workplace mental health research.Methods: We have reviewed several publications and journals from the past 5 years by conducting data searches on Google Scholar in May 2024. It is related to ethical issues concerning informed consent in mental health research in the workplace. We utilized keywords such as mental health research, ethical issues, informed consent, and workplace during the search.Results: The literature review discusses the importance of obtaining informed consent in mental health research in the workplace. It highlights ethical dilemmas faced by employees in disclosing mental health issues, emphasizes the need for cultural sensitivity, and stresses the ethical responsibility of employers to provide mental health support. The review also addresses the significance of ethical issues in designing and assessing mental health interventions and emphasizes the ethical obligation to improve the quality of life for individuals with severe mental illnesses and coexisting somatic conditions in community mental health services.Conclusion: Obtaining informed consent for mental health research in the workplace presents intricate ethical challenges. These include the need to ensure voluntary participation, maintain confidentiality, promote understanding of the research, and navigate workplace dynamics. Researchers are tasked with developing consent procedures that honor participants’ autonomy while also addressing their unique needs and concerns.